PERAN ORANG TUA TERHADAP PRESTASI BELAJAR PESERTA DIDIK DI SMP NEGERI 2 MEGO - Wea, Ludvina Yentiana; Fitri, Mohamad; Chotimah, Nur (Teaching and Learning Journal of Mandalika (Teacher) e- ISSN 2721-9666, 2024)
This study aims to find out how the role of parents has on the learning achievement of students at SMP Negeri 2 Mego, how is the learning achievement of students at SMP Negeri 2 Mego. The method used in this research is a qualitative research. The data sources obtained by the author were obtained from observations, interviews and documentation. The results of this study indicate that parents who always pay attention to their children, especially attention in their learning activities at home, make children more active and more enthusiastic in learning. the same one. The role of parents in their children's learning motivation in the learning process, because parents are the basis for educating children in the family. Learning achievement of students can be known through a series of tests, both text and non-tech. To get the achievement of student learning achievement. So the role of parents can provide motivation for students at home including attention to the learning process, giving advice, giving gifts and punishments that educate, and providing learning facilities to students.